HUBUNGAN KEMAMPUAN PEMECAHAN MASALAH DENGAN EFIKASI SISWA MAN DAIRI - Sri Cantika Padang; Isnaniah Isnaniah; Kasmini Maha (Universitas Pahlawan Tuanku Tambusai, 2022)
Problem solving is the most important thing in learning mathematics and plays a very important role in the next era. However, not all students are able to master this problem, therefore further research is needed. The aim of this research was to describe a problem-solving ability with self-efficacy. The method used is descriptive qualitative. The research subjects were taken by 26 students/i XI – IPS 1 Mandairi. From this study there were 2 instruments, namely self-efficacy questionnaires and problem solving questions. This study shows that (1) there are still students who leave blank answers. (2) between problem solving and self-efficacy is still weak where r=0.0648. (3) almost all students have a good level of self-efficacy where the levels range from quite high to very low. Keywords: problem solving ability, self-efficacy